Qualidade nutricional e aceitabilidade da geleia convencional e light de maná cubiu - Furlaneto, Karina Aparecida [UNESP] (2015)
The objective of this work was to develop a light jelly manna cubiu sweetened with sucralose, evaluate its composition and acceptability. In the fresh fruit and bleached pulp manna cubiu were held the following physico-chemical analysis (soluble solids, pH, Acidity, reducing sugar), quantification of instrumental color and chemistries (Phenolic Compounds and Antioxidant Activity Totals by DPPH method). The jellies were prepared with a concentration of 60:40 (pulp crystallized sugar) for conventional and 60:40 (pulp: Crystal + sucralose sugar) for light jellies. For gelation thereof occur, citrus pectin was used. The jelly was bottled in the hot glass containers with a capacity of 320g, pre-sterilized closed and inverted. After filling the jellies were cooled naturally and stored at room temperature. Jelly were asked the following analyzes: Physical and chemical (soluble solids, pH, Acidity, reducing sugar and total reducing sugar), quantification of instrumental color, biochemical (Phenolic Compounds and Antioxidant Activity Totals by DPPH method), and microbiological analysis sensory analysis for the storage period of 120 days. The Soluble Solids content increased during the storage time. The treatments showed that the addition of sweetener (formulations light) caused a small increase of the pH value when compared with the conventional jelly. During the storage period, there was a small increase in Titratable Acidity levels, especially in light formulations. The Phenolic Compounds Total fell significantly in the first fifteen days of storage for all treatments, as the antioxidants did not change significantly during storage. The results of the gel did not show any microbiological contamination until 120 days of storage, appearing in satisfactory sanitary conditions. The Jelly Light 2 (60% + 28% sucrose pulp + 12% sucralose), showed greater acceptance and according to the assessment of purchase ...